OPTIMIZATION OF THE COAL HANDLING FACILITY LINE FOR COAL SUPPLY TO A COAL-FIRED POWER PLANT - Raden Muhammad Fauzih; Nur Budi Mulyono (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The Coal Handling Facility (CHF) functions as the principal conveyor line responsible for delivering coal to the coal-fired power plant. Coal extracted from the mining face is transported by dump trucks over an average distance of approximately five kilometers before being transferred to the conveyor system, which subsequently channels the coal to the power plant. In parallel, overburden materials are transported to designated disposal sites located about four kilometers from the mining area. These operational conditions underscore the necessity of optimizing the CHF route to enhance overall system efficiency. This study investigates the operational constraints and develops strategies for improving coal supply chain performance to the power plant. The research employs the Six Sigma methodology, utilizing its structured problem-solving framework : Define, Measure, Analyze, Improve, and Control (DMAIC), to propose optimization measures aimed at enhancing efficiency and reducing operational costs for the company. Keywords: Coal Handling Facility (CHF); Coal fired Power Plant; Conveyor; Six Sigma; Cost Reduction; Define, Measure, Analyze, Improve, and Control (DMAIC)